Measuring the effects of University-Firm cooperation on the firm's innovative performance: evidence from Spain - Jose Polo; Néstor Duch; Martí Parellada (European Regional Science Association (ERSA), 2011)
In this paper we empirically analyze the effects of collaboration in innovation with universities on the firm's innovative performance. Using data from the Technological Innovation Panel dataset (PITEC for its acronym in Spanish) we have constructed a database of 4643 innovative firms in Spain, where we estimate the impact of different types of collaborative partnerships on the increments on firm's range and quality of products, and on the improvements of the firm's production capacity and flexibility. The estimation from an ordered logit model shows that firms collaborating actively with universities, as well as, firms that use universities as their principal source of information are more prone to have product and process additionalities, while subcontracting specific R&D activities to universities do not seem to affect the firm's innovative performance. A sensitive analysis shows that firms belonging to manufacturing sectors benefit more from the collaboration with universities than firms from services sectors.
Keywords: 330